2006
DOI: 10.1097/01.nmd.0000222406.16820.13
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fantasy Proneness and Schizotypy in Adolescents

Abstract: Previous research has found substantial relationships between fantasy proneness and schizotypy in adulthood. The aim of the present study is to examine the connections between these constructs in an adolescent sample. A sample of 511 adolescents filled out a measure of fantasy proneness and a measure of psychotic-like phenomena. The factorial pattern for schizotypal traits in adolescents replicate the earlier documented three-factor structure. Also, the full range of schizotypal features was found to be relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…Our results are consistent with the view that 'fantasy' converges with delusionproneness, cognitive-perceptual aberrations and disorganized features [73]. Pronounced 'fantasy' may indicate some vulnerability for schizophrenia [74], but might represent a reasoning style like cognitive slippage or perceptual immersion that is normally distributed in the population and pronounced in at-risk populations, and but has to interact with attributional biases in order to result in psychosis [75].…”
Section: Specificity Of Social-cognitive Deficitssupporting
confidence: 90%
“…Our results are consistent with the view that 'fantasy' converges with delusionproneness, cognitive-perceptual aberrations and disorganized features [73]. Pronounced 'fantasy' may indicate some vulnerability for schizophrenia [74], but might represent a reasoning style like cognitive slippage or perceptual immersion that is normally distributed in the population and pronounced in at-risk populations, and but has to interact with attributional biases in order to result in psychosis [75].…”
Section: Specificity Of Social-cognitive Deficitssupporting
confidence: 90%
“…The CEQ (Cronbach's alpha = 0.79; Merckelbach et al, 2001a;Sánchez-Bernardos & Avia, 2004, 2006) is a self-report measure of fantasy proneness. It comprises 25 yes-no items that were derived from extensive case descriptions of fantasy proneness provided by Wilson and Barber (1983).…”
Section: Ceqmentioning
confidence: 99%
“…For example, adolescents who have report psychotic-like experiences are also more likely to manifest difficulty concentrating, irritability, hypersensitivity to noise, sleep disturbances, suicidal ideation and attempts, and heightened anxiety (Nishida et al 2008). Another recent investigation examined the relation of fantasy proneness, a common tendency in youth, with schizotypal symptom ratings (Sanchez-Bernardos and Avia 2006). The authors found that fantasy proneness correlated with the positive features of schizotypy, namely the magical ideation and the cognitive-perceptual dimensions, but not with the interpersonal symptoms, such as social anxiety.…”
Section: Cluster a Personality Disorders In Childhood And Adolescencementioning
confidence: 99%